Population structure, molecular and physiological characterisation of elite wheat varieties used as parents in drought and heat stress breeding in India - Ramya, P.; Jain, N.; Singh, P.K.; Singh, G.P.; Prabhu, K.V. (The Indian Journal of Genetics and Plant Breeding, 2016)
In the present study 24 modern cultivars of wheat were subjected to genetic and physiological characterisation in order to ascertain their use as parents in drought and heat tolerance breeding. The physiological traits, canopy temperature and chlorophyll content of flag leaves were found to be widely distributed. Population structure analysis grouped them into seven clusters with optimum k value=7. AMOVA and PCoA (Principal Coordinate Analysis) revealed higher level of polymorphism among the resistant and susceptible groups. The study revealed that the varieties used in breeding program are highly divergent pure breeding lines with unique pattern of alleles.